1993
DOI: 10.1007/bf03190181
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of functional liver plasma flow in ICU patients by a modified hepatic D-sorbitol plasma clearance method

Abstract: Changes in liver perfusion may have a substantial influence on the pharmacokinetics of drugs with flow-controlled metabolism. This may have important implications for drug dosage in patients in an intensive care unit (ICU). The hepatic D-sorbitol plasma clearance has been suggested as a non-invasive test for evaluating functional liver plasma flow, which is in reasonable agreement with the direct blood measurement. However, its determination requires D-sorbitol infusion for 3 h or administration of a D-sorbito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[2][3][4]7,9,10 One earlier study of patients with severe ALF (information about presence of HE was not given), where flow was estimated by use of systemic sorbitol clearance, it was concluded that hepatic plasma flow was low; around 450 mL/min. 1 As seen from Table 2, a clearance method will grossly underestimate hepatic plasma flow because it requires that E equals 1. When the methodology with liver vein catheterization was applied, we found that hepatic plasma flow was clearly elevated.…”
Section: Pathophysiological Significance Of Elevated Hepatic Plasma Fmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4]7,9,10 One earlier study of patients with severe ALF (information about presence of HE was not given), where flow was estimated by use of systemic sorbitol clearance, it was concluded that hepatic plasma flow was low; around 450 mL/min. 1 As seen from Table 2, a clearance method will grossly underestimate hepatic plasma flow because it requires that E equals 1. When the methodology with liver vein catheterization was applied, we found that hepatic plasma flow was clearly elevated.…”
Section: Pathophysiological Significance Of Elevated Hepatic Plasma Fmentioning
confidence: 99%
“…A single study indicated that estimated hepatic plasma flow (EHPF) was low, i.e., 450 mL/min in patients with ALF. 1 Studies in patients with CLF without HE have reported either normal or decreased EHPF in this condition. [2][3][4] The lack of solid data in this field is primarily a method problem.…”
mentioning
confidence: 96%
“…14 15 However, the shunt fraction measured by radiolabelled microspheres is limited by the 15 µm diameter of microspheres used, and by definition, blood flow through small shunts (<15 µm) is excluded. Most clearance methods currently available for human studies, including sorbitol clearance, require long infusion times, numerous large volumes of blood, [16][17][18][19][20] and are thus unsuitable for use in small animals such as the rat.…”
mentioning
confidence: 99%
“…Sorbitol was selected because it is safe, easy to measure, and has a high extraction ratio in the normal liver without interference from glucose. [16][17][18][19] Thus the aims of the present study were to determine: (i) the proportion (shunt fraction) of intrahepatic shunt flow in the normal rat liver following intrahepatic portal occlusion by microspheres; (ii) the anatomical origin of these shunts in the normal liver; and (iii) the site of confluence between the hepatic artery and portal vein.…”
mentioning
confidence: 99%